Pictures on the radio : the work of NPR photojournalist David P. Gilkey - Gilkey, David P.; Somodevilla, Chip; Zambelich, Ariel (powerHouse Books, 2020)
Compiles the work of David Gilkey, a celebrated conflict photographer who helped NPR bring vivid life to big and small stories with global impact. Known for chronicling pain and beauty in war and conflict, he was on assignment in Helmand, Afghanistan in 2016 when he and NPR's Afghan interpreter, Zabihullah Tamanna were killed by a Taliban ambush of their convoy. Considered one of the best photojournalists in the world, his death made headlines around the country and the globe. The nine chapters in 'Pictures on the Radio' include photographs from assignments in Afghanistan, Haiti, and Gaza covering war, natural disasters, and political strife, but also a surreal journey on the tran-Siberian railroad, a voyage down the Yamuna, and coverage of American war-veterans showcasing Gilkey's range as a photojournalist whose work captured the strength and fragility of our humanity and our planet. Essays by NPR correspondents--including Jason Beaubien, David Greene, Julie McCarthy, and Eric Westervelt--who accompanied David on assignment introduce each chapter of award-winning photographs. A preface by Alyda Gilkey paints a portrait of the man behind the camera.